2012
DOI: 10.1007/s13191-012-0182-1
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Dimensional Accuracy of One-Step and Two-Step Impression Technique Using Addition Silicone Impression Material: An In Vitro Study

Abstract: The study is aimed to evaluate the dimensional accuracy, the effect of undercut of two different configurations and the elastic recovery of addition silicone impression material assessed indirectly, by measuring the dimensions on stone models recorded from the impression of the master model, using one-step and two-step impression technique, for addition silicone impression materials. Measurements are taken to evaluate horizontal or linear and vertical dimensional changes, of the abutment V and abutment C from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 9 publications
0
21
0
1
Order By: Relevance
“…The in-vitro study of Pande et al [8] aims at evaluating the dimensional accuracy, the effect of undermining in three different abutments and the elastic restoration of the addition silicone by indirect assessment, measuring the dimensions of the cast plaster models obtained by impressions from the master model, using the double-phase 1-step impression and the double-phase 2-step impression. Moreover, measurements were also made to evaluate the horizontal or linear and vertical dimensional changes of the corresponding abutments of the master steel model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in-vitro study of Pande et al [8] aims at evaluating the dimensional accuracy, the effect of undermining in three different abutments and the elastic restoration of the addition silicone by indirect assessment, measuring the dimensions of the cast plaster models obtained by impressions from the master model, using the double-phase 1-step impression and the double-phase 2-step impression. Moreover, measurements were also made to evaluate the horizontal or linear and vertical dimensional changes of the corresponding abutments of the master steel model.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-step double phase technique is performed first by filling up the tray with the putty impression material and record the abutment. The second step continues after setting (hardening) of the impression and its extraction from the mouth where low viscosity material is afterwards applied on the first impression and is again returned into the mouth for correctional impression [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors 8,[10][11][12][13][14][15] have demonstrated that the impression technique is a critical factor which directly influences the dimensional accuracy. However, in this study, the dimensional accuracy of a partially edentulous mandibular arch is related more to the type of impression material than the impression technique 7,[16][17] . The 2-step putty/light-body technique was initially developed to decrease the problems of polymerization shrinkage for condensation silicones 18 .…”
Section: Discussionmentioning
confidence: 77%
“…A ratio of 150 g of type IV dental stone (IV Durone, Dentsply) to 28.5 ml of water was used to fill the molds (n = 5). The sample size was determined according to previous studies 17,[21][22] which demonstrated that 5 samples had an adequate power to detect statistical differences between groups. Three readings were performed for each distance by a single calibrated operator and the means were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation